Effects of a small-sided games training program in youth male soccer players: variations of the locomotor profile while interacting with baseline level and with the accumulated load - Silva, A. F.; Oliveira, R.; Ceylan, H. I.; Akyildiz, Z.; González-Fernández, F. T.; Nobari, H.; Yildiz, M.; Birlik, S.; Clemente, F. M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Purpose This study aimed to (1) analyze the impact of a small-sided game training program in the locomotor profile of youth male soccer players (while interacting with the baseline level - higher and lower level); and (2) test the relationships between variation in locomotor profile and the accumulated demands in 3v3, 5v5 and match over the period of observation.